The Legal framework on foreign investment in Cambodia - David, Sokkhon (KDI School, 2011)
The very rapid economic growth of Cambodia, its dramatic success in world export markets and its heavy receives of foreign direct investment (FDI) have generated much thought and debate in policy and business circles in different parts of the world. And in the Second Socio- Economic Development Plan 2001-2005, the Cambodian government regards foreign direct investment (FDI) as a major engine for economic development. For this reason, the Cambodian government regards foreign direct investment (FDI) as a major engine for economic development. From the viewpoint of the legal framework in Cambodia, laws and regulations governing FDI in Cambodia are basically designed to encourage investments. As the Law on Investment stipulates, FDIs are treated in a non-discriminatory manner except for land-ownership and allowed to invest freely in many areas. Therefore, in order to attract FDI, the Government of Cambodia is trying to create an institutional and regulatory framework, a stable policy, and real free market oriented system. Moreover, after the political stability and peace were born in 1998 in Cambodia, the government recognized foreign investment is essential and that it, can develop the national economy of this country, and rebuild the infra-structures and human resources which were destroyed by the civil war. In addition, the quality of the protection for foreign investment was still inadequate. Hence, the government has structured the politic of integration into the regional (ASEAN) and the World (WTO) in order to obtain the special assistance, and no doubt, to attract foreign direct investment from those two organizations and to enlarge the market. The objective of this thesis is to provide a comprehensive exploration of trade policy and specifically, to understand the system of legal framework on foreign investment in Cambodia. The main question of this research thesis is whether how can the Cambodian government harmonize the international law and national law in order to attract foreign investment? With the proper legal framework, Cambodia will become a very competitive country for foreign direct investment, with a liberal business environment, non-discrimination, low cost and hard working labor force. The government of Cambodia will continue to attract companies from around the world to invest and to do business in Cambodia because FDI has played an important role in rehabilitating Cambodia’s economy.
Thesis(Master) --KDI School:Master of Public Policy,2011
Keywords: Cambodia.